UPAYA PEMBERIAN PELAYANAN PUBLIK DI UPT PUSKESMAS BALAI MAKAM KABUPATEN BENGKALIS - afrizal, dedy; effendi, nahar; handayani, pertiwi (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2019)
Public services provided by service providers must be synchronized with act no.25 of 2009 on public services in which there are stipulation of services, goods services, and administrative services for the society. The technical services unit (upt) of the puskesmas balai makam subdistrict of bathin solapan, bengkalis regency is a type of non-inpatient puskesmas under the supervision of the bengkalis district health service that provides services to the society, especially health services, however the facilities and infrastructure are not well implemented, payment system is not in accordance with the standard, and the problem of lack of availability of medicines for people who need health services. This study will elaborate the conduct of the services at how the implementation of services, supporting factors and inhibiting factors of health services. The result of the study will refer to the implementation of 5 indicators such as tangibles, reliability, responsiveness, assurance, emphaty are obtained a total score of 3,974 (88.31%) for the good category